Zoonotic Dirofilaria sp. “hongkongensis” in subcutaneous nodules from dogs and cats, Hong Kong SAR - Thamali Manathunga; May Tse; Livia Perles; Frederic Beugnet; Vanessa Barrs; Domenico Otranto (Parasites & Vectors)
Abstract Background Dirofilaria sp. “hongkongensis” is a putative Dirofilaria species, initially identified in subcutaneous nodules in humans in Hong Kong and in other South and Southeast Asian regions. While it differs genetically from the better-known zoonotic species, Dirofilaria repens and Dirofilaria immitis, information on the lesions caused by Dirofilaria sp. “hongkongensis” in the hosts as well as on its biology is scarce. This study documents for the first time the presence of this filarioid nematode in subcutaneous nodules in dogs and cats in Hong Kong, where it was originally described in human patients, therefore providing evidence for the zoonotic nature of this parasite. Methods Records of Veterinary Diagnostic Laboratory of City University of Hong Kong were searched between 2019 and 2024 for histological reports of possible filarioid-associated lesions. Tissue samples were collected by excisional surgical biopsy and processed with routine paraffin techniques. Selected slides were stained using various staining techniques [i.e., hematoxylin and eosin, periodic acid–Schiff (PAS), Grocott methenamine silver (GMS) or Ziehl–Neelsen (ZN) and Gram stain]. DNA from formalin-fixed paraffin-embedded tissue were extracted, submitted to conventional polymerase chain reaction (cPCR) and sequencing (i.e., cox1 and 12S rRNA genes) and phylogenetic analyzed. Results A total of five subcutaneous nodules from four cats and one from a dog with histopathology suggestive of filariosis were selected. The presence of Dirofilaria sp. “hongkongensis” was morphologically and molecularly confirmed in one dog and one cat. Both histopathological presentation and phylogenetic analysis enabled classification of this species close to D. repens and within the subgenus Nochtiella. In the remaining three cases, one showed histological evidence of aberrant nematode migration, while non-parasitic causes were identified in the other two. Conclusions This study provides the first evidence of Dirofilaria sp. “hongkongensis” in subcutaneous nodules in cats and dogs. The histology of clinical lesions of this filarioid species herein described is closely related to those caused by D. repens. Overall, this species should be considered in differential diagnoses of subcutaneous lesions in both animals and humans in the region. Graphical Abstract